Formation and evolution of discs and bulges through cosmic time in CANDELS - Margalef Bentabol, Berta (2017)
We examine a sample of 1495 galaxies in the UDS/CANDELS field to determine the evolution of two component galaxies, including bulges and discs, within massive galaxies at the epoch 1 < z < 3 when the Hubble sequence forms. We fit all of our galaxies’ light profiles with a single Sérsic fit, as well as with a combination of exponential and Sérsic profiles. The latter is done in order to describe a galaxy with an inner and an outer component, or bulge and disc component. We develop and use three classification methods (visual, F-test and the RFF) to separate our sample into 1-component galaxies (disc/spheroids-like galaxies) and 2-component galaxies (galaxies formed by an ‘inner part’ or bulge and an ‘outer part’ or disc). We then compare the results from using these three different ways to classify our galaxies. We find that the fraction of galaxies selected as 2-component systems increases on average 50% from the lowest mass bin to the most massive galaxies, and decreases with redshift by a factor of 4 from z = 1 to z = 3. We find that single Sérsic ‘disc-like’ galaxies have the highest relative number densities at all redshifts, and that 2-component galaxies have the greatest increase and become at par with Sérsic discs by z = 1. We also find that the systems we classify as 2-component galaxies have an increase in the sizes of their outer components, or ‘discs’, by about a factor of 3 from z = 3 to z = 1.5, while the inner components or ‘bulges’ stay roughly the same size. This suggests that these systems are growing from the inside out, whilst the bulges or protobulges are in place early in the history of these galaxies. We then extend our study to a broader range in wavelength, using all available bands from the HST in the UDS/CANDELS field (H, J, i and V band) in order to calculate rest-frame magnitudes, stellar masses and SFRs for each component. We show that galaxies which are better fit as 2-component systems can have the stellar masses and star formation rates of their inner and outer components measured accurately. We examine the position of our inner/outer components in the UVJ diagram, finding that the majority of both inner and outer components lie in the star forming region (68% and 90% respectively), but that the inner portions, the likely forming bulges, are dominated by dusty star formation. Furthermore, we show that the outer components of these forming galaxies have a higher star formation rate, and the relative star formation rate increases in outer components (or discs) as redshift decreases. On the other hand, the relative stellar mass of both components remains statistically constant at z < 3. This suggests that mass formed in the outer components of galaxies is being transferred to the inner components. Finally, we find that the presence of an AGN is more common in both 1-component spheroid-like galaxies and 2-component systems (13 ± 3% and 11 ± 2%) than in 1-component disc-like galaxies (3 ± 1%), demonstrating that the formation of a central inner component likely triggers the formation of the central massive black holes in these galaxies. Lastly we explore the properties of spiral galaxies in UDS, GOODS-S and COSMOS CANDELS fields. We use the CANDELS Galaxy Zoo classification to select spiral galaxies, clumpy spiral and smooth discs. We show that galaxies classified as spirals decrease with increasing redshift, although part of this trend is due to redshift effects. After correcting such effects, we find that the number density of spirals galaxies increases by a factor of 14 ± 2 from z = 2.5 to z = 0.5. We find morphological differences between spiral galaxies and smooth discs, with the former being more ‘disky’ and asymmetric, and the latter being more centrally concentrated. We show that spiral galaxies, and in particular clumpy spirals, dominate the star formation at all redshifts, with average SFRs of SFR = 40 ± 3 Moyr−1 and SFR = 50 ± 7 Moyr−1 respectively, and that there is no benefit of having a large mass to produce spiral structures.